Features of the linguistic situation in a multilingual area (the case of Rutulsky District of the Republic of Dagestan) - Ataev, Boris M.; Ibragimova, Mariza O. (The New Research of Tuva, 2022)
The article analyzes the linguistic situation in Rutulsky District of the Republic of Dagestan. Its features include ethnic diversity and multilingualism. Native speakers of six East Caucasian and Turkic languages (that are heterogeneous in their genetic characteristics) live in a relatively small area of the district. Russian is the official language of record keeping and interethnic communication there. The relevance of the research topic stems from the need to monitor trends in the development of a unique language community through the example of a particular region. The unique character of the language situation in the district is due to the combination and variation of its constituent criteria: the history of its origin, political, demographic and economic prerequisites for its formation, features of the spheres of functioning of the languages, the current state of contacts between speakers of structurally different languages through the Russian language. Some of the features are associated with the discrepancy between the present-day dwelling area of some ethnic groups inhabiting Rutulsky District and their historically native areas. The specificity of dialects and subdialects spoken by the Avars, Laks and Azerbaijanis living in the area makes it impossible for their speakers to fully communicate with representatives of the respective nationalities. Interestingly, the change of the language of interethnic communication has occurred over the past half century: the Azerbaijani language has been completely displaced by Russian. Thus, the issues of preserving native languages common to many regions of Russia are generally relevant for the ethnically heterogeneous and multilingual Rutulsky District. Nevertheless, in this case we are talking about the preservation of newly written languages (Rutul and Tsakhur) and specific dialects and subdialects of the Lak, Avar and Azerbaijani languages represented only on the territory of the study area.